THE CRITICAL INTERPRETATION OF THE AMERICAN DREAM IN F. SCOTT FITZGERALD’S THE GREAT GATSBY - Amirova Zulayxo (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the critical interpretation of the American Dream in The Great Gatsby by F. Scott Fitzgerald. It explores how the Dream transforms from an ideal of hope into an illusion shaped by materialism and inequality. The study focuses on key themes such as social class, moral decay, and illusion versus reality. The findings reveal that the American Dream becomes unattainable and destructive in the context of the Jazz Age.